PENINJAUAN UPAH HUKUM POSITIF PERSPEKTIF DOKTRIN EKONOMI ISLAM MENGENAI UPAH SYARIAH - Ferricha, Dian (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
The realization of a good investment climate, one of them with a conducive industrial relations. The current wage system is still not completely answer the problems of wages is complex, given the rise of workersâ demands related to wages in each year which impact on the weakness of the economy in Indonesia. That requires an alternative solution to the problem of wages complex answer through the fulfllment of the principle of remuneration in accordance with the conditions and needs of workers / laborers Indonesia. Answering the above problems can put the knowledge to be a solution. One applicative knowledge that can address the problems of wages through sharia. Through normative juridical research method with a prophetic approach based on legal materials normative-prescriptive, this study aims to analyze the wage review of the positive law doctrine of Islamic economics perspective on wages sharia. It is intended that knowledge can also contribute solutions to the economic problems in Indonesia, especially in the realm of industrial relations.Keywords: review of wages, positive law, the doctrine of Islamic economics